Consciousness about HIV/AIDS and STIs among women in Bangladesh: A cross-sectional study - Hossain, Mosharaf; Mat Min, Ruhani; K. C. Mani, Kulanthayan (Teikyo University School of Medicine, 2021)
Consciousness about HIV/AIDS and STIs has become one of today major challenges. The aim of this study was to identify the risk factors associated with awareness about HIV/AIDS and STDs among women in Bangladesh. To conduct this cross-sectional study, data were gathered from the Bangladesh Demographic and Health Survey (BDHS) 2014. The total number of women participants was 17,684 from seven divisions of Bangladesh: Dhaka, Rajshahi, Rangpur, Chittagong, Barisal, Khulna, and Sylhet. The prevalence of consciousness about HIV/AIDS and STIs among women in Bangladesh is 50.1% and 51.2%, respectively. The 2 test showed that the respondent’s age, place of residence, educational level, geographical difference, socio-economic status, radio, and television had a significant association with consciousness about HIV/AIDS and STIs. The multiple logistic regressions identified the risk factors – age of respondents, place of residence, educational level, socioeconomic status, geographical difference, listening to the radio, and watching television (TV) – with the consciousness among women in Bangladesh about HIV/AIDS and STIs. It is essential to increase the educational programmes concerning HIV/AIDS and STIs for rural areas in Bangladesh, especially for the younger women (<25 years). Radio and television play significant roles in increasing consciousness regarding HIV/AIDS and STIs in the rural areas of Bangladesh. The Bangladesh Government should consider including information about HIV/AIDS and STIs in primary and secondary school textbooks.